Digital Pesantren: Revitalization of the Islamic Education System in the Disruptive Era - Cecep Nikmatullah; Wawan Wahyudin; Naf'an Tarihoran; Anis Fauzi (Institut Agama Islam Negeri Kendari, 2023)
This study aims to identify the system of Islamic education faced by the Pesantren during the period of upheaval. This study is a preliminary qualitative study aimed at analyzing various literature on the critical issues of Pesantrens during the period of disruption. The data obtained in this study were collected using documentation methods and subsequently validated using source triangulation techniques. Data analysis was conducted in three stages: data reduction, presentation, and conclusion formulation. The study revealed the following. (1) Pesantrens will activate the Islamic education system by expanding the scope of the santri through extracurricular activities according to the interests and talents of the santri. Pesantrens will focus on all areas of life (Internet of Things), big data, and artificial intelligence for information gathering and knowledge transfer. (2) The Role of Pesantrens in an era of disruption following Advances in Science and Technology. Islamic education still depends on three terms – tarbiyah, ta’lim, and ta’dib – and the use of each has many implications. The role of science and technology can be fulfilled through innovation, teaching methods and media. (3) The digital needs of a disruptive age in Pesantrens can make accessing information and knowledge easier for the santri. Changes in Islamic education will be examined, particularly the medium of instruction, teaching methods, and the Islamic curriculum in the digital age. (4) Solves the problems of the system of Islamic education in Pesantrens by adapting and restructuring it to the social requirements and challenges of the digital age based on Islamic principles. The strategies of the project are: improving Pesantrens based on values, improving the human resources of Pesantrens, improving the material and technical base of Pesantrens and the development of Pesantren curricula